2011
DOI: 10.1007/s10661-011-2084-9
|View full text |Cite
|
Sign up to set email alerts
|

Ground level volume mixing ratio of methane in a tropical coastal city

Abstract: Urban regions are hotspots of greenhouse gas emissions which include CO(2), CH(4), N(2)O, etc. Methane is a strong greenhouse gas which is produced from a number of sources including fossil fuel combustion, municipal waste, and sewage processing, etc. Ground level mixing ratio of methane in the tropical coastal city of Thiruvananthapuram in South India, during calm early morning period was measured. Measurements were done during both winter and summer seasons. Concentrations were significantly higher than glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…It was seen in this study that the vertical profile of CH 4 concentration within the urban canopy layer was neutral during stable pre-dawn conditions. It is also observed that the spatial distribution of the ambient methane exhibits sensitivity to urban environment [23]. Urban influences in the atmospheric concentration of other trace gases have also been detected.…”
Section: Resultsmentioning
confidence: 91%
“…It was seen in this study that the vertical profile of CH 4 concentration within the urban canopy layer was neutral during stable pre-dawn conditions. It is also observed that the spatial distribution of the ambient methane exhibits sensitivity to urban environment [23]. Urban influences in the atmospheric concentration of other trace gases have also been detected.…”
Section: Resultsmentioning
confidence: 91%
“…The spatial variations in atmospheric CH 4 concentration result from the activities performed at the study sites (Sahay and Ghosh, 2013; Majumdar et al, 2017; Thomas and Zachariah, 2012). Possible sources of CH 4 in the city of Tandil are the sanitary landfill, the sewage treatment plant, the urban lake, vehicular transport, pipeline distribution, and NG consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Once we excluded both the effect of biogenic sources and the accumulation of atmospheric CH 4 by thermal inversion, the rapid increase in the atmospheric CH 4 concentration in fall and winter might be related to diffuse and nonbiogenic sources, such as vehicular transport, NG distribution, and NG consumption, as it was observed in other cities (Thomas and Zachariah, 2012; Phillips et al, 2013; Chamberlain et al, 2016; Sanchez et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future changes in surface temperatures and precipitation have the potential to dramatically alter natural methane fluxes from large Arctic reservoirs (Damm et al, 2010;Kort et al, 2012) and tropical wetlands (Dlugokencky et al, 2009), while transformational changes in anthropogenic emissions from fossil fuel production threaten to further increase atmospheric methane abundance (Larsen et al, 2015). Examples of anthropogenic sources of methane include the natural gas and oil supply chains (production, storage, transmission, distribution, consumption), agricultural activities (enteric fermentation, manure management, rice cultivation), landfills, coal mining, stationary and mobile combustion, and wastewater treatment (Thomas and Zachariah, 2012). This work focuses on anthropogenic point source emitters rather than more diffuse area sources, given that the former are Figure 6.…”
Section: Anthropogenic Methanementioning
confidence: 99%